Design and Build Voltage and Current Monitoring Parameters Device of Rechargeable Batteries in Real-Time Using the INA219 GY-219 Sensor - Bayu, Bayu Jiah Setiawan; Gurum, Gurum Ahmad Pauzi; Agus, Agus Riyanto; Surtono, Arif (Journal of Energy, Material, and Instrumentation Technology, 2023)
Research on the manufacture of devices for monitoring battery voltage and current parameters has been carried out and developed using different types of sensors. This research have been released a device that can monitor battery voltage and current parameters in real time in the charge and discharge process using one sensor. The device is made using a microcontroller in the form of an Arduino Mega XPro 2560 R3, with an input in the form of an INA219 GY-219 sensor to monitor battery voltage and current. The output of device is in the form of automatic control of the charge and discharge circuit through the LCD and relay to obtain data from monitoring the battery voltage and current parameters. The batteries used as materials to be tested in this study are rechargeable Li-ion types. The device can monitor the voltage and current parameters of the battery as it should and can work automatically according to the control program created and designed by the manufacturer. Based on the test results of the INA219 GY-219 sensor in reading the voltage, the average sensor accuracy level is 99.96%, the sensor error average rate is 0.034%, and the sensor precision average is 99.97%. Meanwhile, in the reading current, the average sensor accuracy level is 98.39%, the sensor error average rate is 1.608%, and the sensor precision average is 98.98%.